Impact Evaluation of the Egyptian Health Sector Reform Project : Pilot Phase - Grun, Rebekka; Ayala, Javier (World Bank, Washington, DC, 2013)
In 1997, the Government of Egypt (GoE) launched the Health Sector Reform Program (HSRP). Under the program, persistent needs in maternal and child health were addressed through an emphasis on primary health care, as well as through the introduction of the family health model as the principle of primary care. The World Bank, in co-operation with the Technical Support Office (TSO) of the HSRP at the Ministry of Health (MoH), has conducted an impact evaluation of the different interventions under the reform, focusing on the service delivery component. The evaluation has examined the impact of the HSRP on targeting those in need; coverage and utilization of primary health care, its quality of service and maternal and child health. It has also compared costs and benefits of the interventions and derived lessons for policy going forward. Key suggestions include: 1) human resource development should be extended to include staffing mechanisms, 2) supervision of Quality of Care could be strengthened locally through empowering citizens, 3) a co-payment can support a shift towards primary care, if designed carefully, and 4) the lack of impact of the HSRP on antenatal and natal care warrants re-thinking the focus of outreach activities.